2009
DOI: 10.1002/bem.20499
|View full text |Cite
|
Sign up to set email alerts
|

Features of anti‐inflammatory effects of modulated extremely high‐frequency electromagnetic radiation

Abstract: Using a model of acute zymosan-induced paw edema in NMRI mice, we test the hypothesis that anti-inflammatory effects of extremely high-frequency electromagnetic radiation (EHF EMR) can be essentially modified by application of pulse modulation with certain frequencies. It has been revealed that a single exposure of animals to continuous EHF EMR for 20 min reduced the exudative edema of inflamed paw on average by 19% at intensities of 0.1-0.7 mW/cm(2) and frequencies from the range of 42.2-42.6 GHz. At fixed ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…To eliminate the interference in the plane of an exposed object, an effective multilayer absorbent was placed between the animal container and the floor; therefore, the conditions of exposure were close to free-field conditions. We used the exposure conditions and parameters of EHF EMR whose high efficacy has been shown previously (Gapeyev et al 2009;Gapeyev et al 2014): carrier frequency of 42.2 GHz, incident power density (IPD) of 0.1 mW/cm 2 , pulse modulation by a meander signal, a positively defined rectangular wave signal with 50% duty factor, at fixed frequency of 1 Hz. The frequency of the output signal was controlled by a CH2-25 wavemeter (Istok).…”
Section: Ehf Emr Exposurementioning
confidence: 99%
“…To eliminate the interference in the plane of an exposed object, an effective multilayer absorbent was placed between the animal container and the floor; therefore, the conditions of exposure were close to free-field conditions. We used the exposure conditions and parameters of EHF EMR whose high efficacy has been shown previously (Gapeyev et al 2009;Gapeyev et al 2014): carrier frequency of 42.2 GHz, incident power density (IPD) of 0.1 mW/cm 2 , pulse modulation by a meander signal, a positively defined rectangular wave signal with 50% duty factor, at fixed frequency of 1 Hz. The frequency of the output signal was controlled by a CH2-25 wavemeter (Istok).…”
Section: Ehf Emr Exposurementioning
confidence: 99%
“…To eliminate the interference in the plane of an exposed object, an effective multilayer absorbent was placed between the slides and the table; therefore, the conditions of exposure were close to free-field conditions. Exposure conditions and parameters of EHF EMR whose high efficacy has been shown previously [7] were used: carrier frequency of 42.2 GHz, incident power density of 0.1 mW/cm 2 , continuous generation mode or pulse modulation by a meander signal, a positively defined rectangular wave signal with 50% duty factor, at fixed frequency of 1 Hz. Dosimetric tests were conducted as described earlier [9,10]; the surface specific absorption rate was about 1.5 W/kg at an incident power density of 0.1 mW/cm 2 .…”
Section: Emr Exposure and Treatment With Hydrogen Peroxidementioning
confidence: 99%
“…We have shown that the exposure of animals with local and systemic inflammation to EHF EMR with certain physical parameters induced pronounced anti-inflammatory effects [6,7]. The anti-inflammatory effects of EHF EMR were accompanied with significant decrease in DNA damage of peripheral blood leukocytes and neutrophils [8].…”
Section: Introductionmentioning
confidence: 96%
“…As the biological effects of NIR can also be recorded at intensities much less than their thermal threshold (Adey, 1981;Devyatkov, 1973;Gapeyev et al, 2009;Grigoryev, 2012;Kaczmarek, 2006;Markov, 2004;Movasaghi et al, 2007), these effects cannot be explained by hypothesis from the point of the classical thermodynamic characteristics of NIR (Binhi and Rubin, 2007;Foster, 2006). Because of this, the elucidation of the mechanism of biological effects of NIR on cells and organisms still remains as one of the core problems of modern magnetobiology.…”
Section: Introductionmentioning
confidence: 96%